Pembenaran Menurut Pemikiran Reformasi dan Konsili Trente serta Implikasinya Bagi Kekristenan Modern - Markes, Karlitu Dias; Tubagus, Steven; Objantoro, Enggar (Institut Agama Kristen Negeri Kupang, 2025)
This research examines one of the theological issues that is considered as a central issue in the study of Christian theology, namely Justification. The main focus of the study of justification in this research is directed to the debate between the thoughts of reform theolog, especially Martin Luther, and the decisions of the Council of Trent regarding the issue of justification by faith. This study uses a qualitative descriptive method by conducting a literature review of several scientific works, both books and articles, whose topics of study are related to theological subject matter, namely justification by faith according to the Council of Trent and Protestant Reformation thought. The findings of this study are that in essence the two opinions have the same starting point regarding the concept of justification as God's gift, but the basic difference is that Luther's thought as a reformer wanted to release the concept of justification as God's sovereign gift from all human intervention through services or deeds. Good. While the Council of Trent decided in its Decree that it was impossible to separate justification by the grace of God from good works